Humor in Dakwah: A Socio-Pragmatic Study - Fithriyah Inda Nur Abida; I Nengah Sudipa; Ni Luh Nyoman Seri Malini; Luh Putu Puspawati (RIRAI Publisher, 2024)
This study aims at analyzing the forms, functions, and meanings of humor used by preachers in delivering religious sermons. This study uses a qualitative descriptive method that focuses on the act of identifying, classifying, analyzing data that has been obtained, and describing it in the form of language as it is. Qualitative research emphasizes the depth of data with the researcher as a key instrument in the research. The research data consists of humorous utterances delivered by preachers in Islamic religious sermons, namely Ustadz Anwar Zahid, Ustadz Wijayanto, and Ustadz Da'as Latif. The form of humor is analyzed using morphosyntax theory, the function of humor is linked to sociolinguistic theory, while the meaning of humor is dissected using semantic and pragmatic theory. The results of the study show that there are five dominant forms of humor that appear in dakwah humor, namely line humor, dialogue, stories, poems, and wordplay. The use of humor as a strategy in dakwah is proven to be effective in achieving its communicative goals. Humor helps make religious messages easier to understand and remember by the audience. This is because humor can simplify complex concepts and make them more interesting for listeners. This study also found that humor is not only a form of entertainment, but also an effective communication tool in spreading religious teachings.